Potret Politik Pembangunan Ekonomi Kampung Maredan 2014-2016 - Khairul Anwar (Nakhoda: Jurnal Ilmu Pemerintahan, 2017)
This study aims to describe the economic development of Maredan kampong 2014-2016. This research uses R.William Liddle (2004) conceptualization that is “Restricted Pluralism”. This political analysis is included in the pluralist paradigm of modern political economy. In this analysis, research attempts to answer the main questions, such as whether Maredan village economic development politics? This question is answered by identifying: (1) What are the preference and preferences of building a penghulu? What is the position of the actor in the village development policy process? The results of this study revealed that The choice of Maredan village development policy is determined by the actions of the village heads and institutions in linking the market and the will of the government as a manifestation of the inherent authority. The ability to “reconcile” these two interests is the current policy of village development in Maredan. There are many issues of governance and village development That appear on the surface. But the most prominent political color of economic development in Maredan is the economic factor that affects Maredan society.